高速高性能电主轴热态性能分析 - 毕江涛; 陈小安; 李云松 (Jixie chuandong)
Based on the power flow model of high speed motorized spindle,by using tribology and electromagnetics theory,the heat rate of bearing and the electromagnetic loss of built-in motor are respectively calculated.Utilizing the heat transfer theory,the thermal boundary conditions of spindle are calculated.On this basis,the finite element analysis model of the motorized spindle is built and calculated.The results show that front bearing,front end of spindle and stator are the most serious parts of temperature rise for motorized spindle;and in the initial stage of spindle operation,temperature rise of spindle is the fastest.Therefore in order to improve the spindle thermal characteristics,not only cooling device should be added in the serious parts of temperature rise,but also in the start-up phase,the motorized spindle should be cooled and lubricated effectively.